Oxygen Vacancy-rich Mesoporous Silica KCC-1 for CO2 Methanation - M. Y. S., Hamid; M. L., Firmansyah; S., Triwahyono; A. A., Jalil; R. R., Mukti; E., Febriyanti; V., Suendo; Setiabudi, H. D.; M., Mohamed; W., Nabgan (Elsevier Ltd, 2017)
Mesoporous silica KCC-1 was successfully synthesized by microemulsion system coupled with microwave-assisted hydrothermal method. Mesoporous silica KCC-1 exhibited spherical morphology surrounded with dendritic fiber with the particle size of 200–400 nm and BET surface area of 773 m2/g. Mesoporous silica KCC-1 has significantly higher number of basicity and oxygen vacancy than those of MCM-41 and SiO2 which directly correlated with the catalytic performance of the catalyst. The activity of mesoporous silica KCC-1 in CO2 methanation is five-fold higher than MCM-41 with the yield of CH4 reached 38.9% at 723 K.